Polymorphisms analysis of the Plasmodium ovale tryptophan-rich antigen gene (potra) from imported malaria cases in Henan Province - Ruimin Zhou; Ying Liu; Suhua Li; Yuling Zhao; Fang Huang; Chengyun Yang; Dan Qian; Deling Lu; Yan Deng; Hongwei Zhang; Bianli Xu (Malaria Journal, 2018)
Abstract Background Plasmodium ovale has two different subspecies: P. ovale curtisi and P. ovale wallikeri, which may be distinguished by the gene potra encoding P. ovale tryptophan-rich antigen. The sequence and size of potra gene was variable between the two P. ovale spp., and more fragment sizes were found compared to previous studies. Further information about the diversity of potra genes in these two P. ovale spp. will be needed. Methods A total of 110 dried blood samples were collected from the clinical patients infected with P. ovale, who all returned from Africa in Henan Province in 2011–2016. The fragments of potra were amplified by nested PCR. The sizes and species of potra gene were analysed after sequencing, and the difference between the isolates were analysed with the alignment of the amino acid sequences. The phylogenetic tree was constructed by neighbour-joining to determine the genetic relationship among all the isolates. The distribution of the isolates was analysed based on the origin country. Results Totally 67 samples infected with P. o. wallikeri, which included 8 genotypes of potra, while 43 samples infected with P. o. curtisi including 3 genotypes of potra. Combination with the previous studies, P. o. wallikeri had six sizes, 227, 245, 263, 281, 299 and 335 bp, and P. o. curtisi had four sizes, 299, 317, 335 and 353 bp, the fragment sizes of 299 and 335 bp were the overlaps between the two species. Six amino acid as one unit was firstly used to analyse the amino acid sequence of potra. Amino acid sequence alignment revealed that potra of P. o. wallikeri differed in two amino acid units, MANPIN and AITPIN, while potra of P. o. curtisi differed in amino acid units TINPIN and TITPIS. Combination with the previous studies, there were ten subtypes of potra exiting for P. o. wallikeri and four subtypes for P. o. curtisi. The phylogenetic tree showed that 11 isolates were divided into two clusters, P. o. wallikeri which was then divided into five sub-clusters, and P. o. curtisi which also formed ...